Noonan's syndrome and neurofibromatosis. Issue 2 (February 1987) - Shuper, A; Mukamel, M; Mimouni, M; Steinherz, R
Abstract : A child with Noonan syndrome and multiple cafe au lait spots, compatible in size and number with von Recklinghausen's neurofibromatosis, is presented. These features may represent a distinct genetic entity rather than the coincidence of two diseases.